Perbandingan Pengaruh Penambahan Bakteri Bacillus Megaterium dan Bacillus Subtilis sebagai Self-healing Agent pada Campuran Beton - Agung Suhud Pangestu; Alif Sandika (Institut Teknologi Adhi Tama Surabaya, 2025)
Conventional concrete often experiences cracks that can cause a decrease in structural strength and environmental resistance. Self-healing concrete technology is present as an innovative solution by utilizing the biological ability of bacteria to produce calcium carbonate deposits that can close cracks. This study aims to compare the effect of using bacillus megaterium bacteria and bacillus subtilis bacteria in concrete as self-healing concrete agents in repairing micro cracks automatically. The comparison was made on concrete with a design quality of 25 Mpa, 35 Mpa, and 45 Mpa, each of which was given bacillus megaterium bacteria or bacillus subtilis bacteria. The parameters analyzed include resistance or increased compressive strength. In theory, concrete with bacteria has the ability to close cracks automatically and maintain its structural strength compared to conventional concrete. This shows the great potential for the application of self-healing concrete technology in increasing the service life of concrete structures and reducing long-term maintenance costs.